Kesiapan Mahasiswa Lembaga Pendidikan dan Tenaga Kependidikan (LPTK) di Lombok Menjadi Guru MI/SD - Muhammad Munir; Muhammad Alwan; Husairi Husairi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2022)
The purpose of this study is to describe the readiness of higher education LPTK students in Lombok to become professional MI/SD teacher candidates in terms of knowledge, practice, and attitude, as well as to describe the dominant factors that hinder the readiness to become professional MI/SD teacher candidates. This type of research is quantitative survey method. Instruments for collecting test data, questionnaires, and observation sheets. This study aims to obtain an overview of the characteristics of the population related to the readiness of students to become professional MI/SD teacher candidates. The population in this research is Mataram State Islamic University and Mataram University. The sampling technique used is area sampling. The results of this study indicate in terms of knowledge about students and how to learn the results of the analysis show an average value of 25.74 in the high category. This shows that students are ready to become MI/D professional teachers. While the questionnaire on the ability to carry out learning when viewed from the average value, which is 136.24 in the high category. In the aspect of perception of being an MI/SD teacher, the average score is 103.60 with the agree category. Furthermore, on the confidence data to become a professional MI/SD teacher, the data analysis results obtained an average of 140.04 with the agree category